2021
DOI: 10.1080/00076791.2021.1893696
|View full text |Cite
|
Sign up to set email alerts
|

Death on the stock exchange: The fate of the 1948 population of large UK quoted companies, 1948–2018

Abstract: This article provides a long-term demographic analysis of the principal members of the population of companies quoted on the UK stock exchanges in 1948. Motivated by theories of natural selection and of corporate governance, it traces the survival records of the 1948 population over the biblical 'threescore years and ten' to 2018. Of the population of 1513 companies in 1948, only 19 survived for the full seventy years. The survival rate, as captured by the half-life of companies in the population, is remarkabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In an early statistical study for a substantial set of firms, Singh (1975) found evidence that 'as a survival strategy, attempting to increase relative profitability may well be inferior to attempting to increase relative size, particularly for larger unprofitable firms'(p. 510). Consistent with this, Meeks and Whittington (2021) show that, with just one exception (Tesco-a 'minnow' in 1948), it has only been very large firms that have survived long periods without being acquired. Bayer paid $63 billion for Monsanto in 2018 'because this promised to make the chemicals group invulnerable to takeover' (Guthrie 2020).…”
Section: Power and Protectionmentioning
confidence: 60%
See 1 more Smart Citation
“…In an early statistical study for a substantial set of firms, Singh (1975) found evidence that 'as a survival strategy, attempting to increase relative profitability may well be inferior to attempting to increase relative size, particularly for larger unprofitable firms'(p. 510). Consistent with this, Meeks and Whittington (2021) show that, with just one exception (Tesco-a 'minnow' in 1948), it has only been very large firms that have survived long periods without being acquired. Bayer paid $63 billion for Monsanto in 2018 'because this promised to make the chemicals group invulnerable to takeover' (Guthrie 2020).…”
Section: Power and Protectionmentioning
confidence: 60%
“…M&A has become by far the most common cause of corporate 'death'. Of the population of larger companies listed on UK stock exchanges in 1948, 83% had been taken over by 2018 (Meeks and Whittington 2021). In the US, the number of businesses listed on the Stock Exchange has roughly halved since 1996 (Tepper and Hearn 2019), mostly as a result of merger.…”
Section: One Apparent Solutionmentioning
confidence: 99%